Maternal Supplementation With Avocado (Persea americana Mill.) Pulp and Oil Alters Reflex Maturation, Physical Development, and Offspring Memory in Rats - Melo, Marilia Ferreira Frazão Tavares de; Pereira, Diego Elias; Moura, Renally de Lima; Silva, Elisiane Beatriz da; Melo, Flávio Augusto Lyra Tavares de; Dias, Celina de Castro Querino; Silva, Maciel da Costa Alves; Oliveira, Maria Elieidy Gomes de; Viera, Vanessa Bordin; Pintado, Maria Manuela Estevez; Santos, Sócrates Golzio dos; Soares, Juliana Késsia Barbosa (Frontiers in Neuroscience, 2019)
Avocado (Persea americana Mill.) is an oleaginous fruit source of fatty acids with high levels of neuroprotective phytocomplexes. The objective of this study was to evaluate the development of reflex and somatic maturation, fatty acid profiles in the brain, and memory in different stages of life in the offspring of dams supplemented with avocado pulp and oil during gestation and lactation. The dams were randomly divided into three groups (n = 15 pups/group), and recieved by gavage supplementation: Control group (CG) - distilled water; Avocado Oil (AO) - 3000 mg avocado oil/kg animal weight, and Avocado Pulp (AP) - 3000 mg avocado pulp/kg animal weight. We performed the following tests: Analysis of Somatic Development and Ontogeny of Postnatal Reflex (T0 to T21), the Open Field Habituation Test and the Object Recognition Test (ORT) in the adolescent (T45) and adult (T90) phases. The cerebral fatty acids content was evaluated at times T0, T21, T45 and T90. The results were analyzed using the statistical program GraphPad Prism and significant statistics were considered when p <0.05. Acceleration of reflex maturation and reflex ontogeny was observed in the offspring of AO and AP fed dams, with the results being more pronounced in the pulp fed group (p <0.05). All groups presented a decrease in the ambulation parameter in the second exposure to the Open Field Habituation Test, at T45 and T90 (p <0.05). In the ORT, the AO and AP offspring presented memory improvements in the short and long term in the adult and adolescent phases (p <0.05). The results of the brain fatty acid profiles presented higher polyunsaturated fatty acids (PUFA) content in the AO and AP groups at T21, T45 and T90. The docosahexaenoic fatty acid (DHA) content was higher at T21 (AO and AP), at T45 (AO and AP), and at T90 (AP) (p <0.05). The arachidonic acid (ARA) content was higher at T45 (AO and AP), and at T90 (AO) (p <0.05). Maternal supplementation with avocado oil and pulp anticipates reflex maturation and somatic postnatal development, and improves memory during the adolescent and adult phases.